Four missense genetic variants in CUBN are associated with higher levels of eGFR in non-diabetes but not in diabetes mellitus or its subtypes: A genetic association study in Europeans - Uglebjerg, Nicoline; Ahmadizar, Fariba; Aly, Dina M.; Cañadas-Garre, Marisa; Hill, Claire; Naber, Annemieke; Oddsson, Asmundur; Singh, Sunny S.; Smyth, Laura; Trégouët, David-Alexandre; Chaker, Layal; Ghanbari, Mohsen; et al. (Frontiers in Endocrinology, 2023)
Genetic variants in the CUBN gene – encoding the main albumin-transporter in the proximal tubule of the kidneys – have previously been associated with microalbuminuria and higher urine albumin levels. However, their relation to the estimated glomerular filtration rate (eGFR) is largely unexplored. We examined the associations between four CUBN variants and eGFRcreatinine in Europeans with Type 1 (T1D) and Type 2 Diabetes (T2D). Furthermore, we sought to deepen our understanding of these variants in a range of single- and aggregate- variant analyses of other kidney-related traits in individuals with and without diabetes mellitus. We carried out a genetic association-based linear regression analysis between four CUBN missense variants (rs141640975, rs144360241 rs45551835, rs1801239) and eGFRcreatinine (ml/min/1.73 m2, CKD-EPIcreatinine(2012), natural log-transformed) in populations with T1D (n ~ 3,588) or T2D (n ~ 31,155) from multiple European studies and in individuals without diabetes from UK Biobank (n ~ 370,061). Summary results of the diabetes-group were meta-analyzed using the fixed-effect inverse-variance method. Albeit we did not observe associations between eGFRcreatinine and CUBN in the diabetes-group, we found significant positive associations between the minor alleles of all four variants and eGFRcreatinine in individuals without diabetes with rs141640975 being the strongest (PeGFR_creatinine=2.2e-9). For rs141640975, the eGFRcreatinine-association showed significant interaction with albuminuria levels (normo-, micro-, and macroalbuminuria). An aggregated genetic risk score (GRS) was associated with higher urine albumin levels and eGFRcreatinine. The rs141640975 was also associated with higher levels of eGFRcreatinine-cystatin C (ml/min/1.73 m2, CKD-EPI2021, natural log-transformed) and lower circulating cystatin C levels. The positive associations between the four CUBN variants and eGFR in a large population without diabetes suggest a pleiotropic role of CUBN as a novel eGFR-locus in addition to it being a known albuminuria-locus. The interaction between rs141640975 and albuminuria-status on eGFRcreatinine in this population and its associations with lower cystatin C and higher levels of eGFRcreatinine-cystatin C expand our knowledge of these variants concerning kidney function measures. The demonstration of a CUBN-focused GRS further suggests an important role of CUBN in the future personalization of chronic kidney disease management.